PEMANFAATAN KOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS) DENGAN BAKTERI SELULOLITIK DAN LIGOLITIK SERTA NPK TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Isna Rahma Dini; Idwar Idwar; Amir Franky Simamora (Perkebunan dan Lahan Tropika, 2019)
Cocoa (Theobroma cacao L.) is one of the large plantations after oil palm. The increase in cocoa nursery can be accompanied by the utilization of waste derived from palm oil, namely oil palm empty fruit bunches (OPEFB). OPEFB can be useful as organic fertilizer because it can improve soil physical, chemical and biological properties. The use of OPEFB as organic fertilizer will also reduce excessive use of NPK. Utilization of OPEFB into organic fertilizer can be in the form of compost or raw OPEFB organic matter plus cellulolytic and lignolytic microbes. This study aims to determine the effect of NPK fertilizer and OPEFB compost on the growth of cocoa seedlings. This research was conducted experimentally using a completely randomized design (CRD) consisting of 9 treatments and 3 replications. Parameters of observation were plant height, stem diameter, number of leaves, root canopy ratio, dry weight of seedlings and age of planting. The results showed that the provision of 100 g/polybag OPEFB compost plus 50% NPK fertilizer (2 g / polybag) could provide good growth in cocoa seeds (Theobroma cacao L.).Keyword : Cocoa, compost, cellulolytic bacteria, lignolytic bacteria, OPEFB